Assessment of ecological state for the north-eastern shelf of Sakhalin Island: hydrochemical analysis and bioassay - Olga N. Lukyanova; Elena V. Zhuravel; Denis N. Chulchekov; Olga V. Podgurskaya (Известия ТИНРО)
Results of ecological monitoring in the coastal waters at north-eastern Sakhalin are presented. Spatial patterns of water temperature, salinity, dissolved oxygen content, and concentrations of inorganic phosphate and silicon are described, geostrophic currents are calculated. Abnormalities of early embryogenesis are revealed for the sand dollar Scaphechinus mirabilis in the water sampled both at the coast and in the oil-producing areas but not in the areas distanced from the oil wells. Possible influence of natural environments and anthropogenic factors on marine biota in the area of monitoring is discussed: the abnormalities at the coast are possibly caused by low salinity, but those ones in the oil-producing areas have no any natural reasons, so far as salinity, temperature and nutrients concentration in these areas are the same as in the open-waters with normal results of the bioassay. Thus, anthropogenic impact on marine biota is detected for the areas of continued oil and gas production on the northeastern shelf of Sakhalin Island.